KRAS Mutation Is a Significant Prognostic Factor in Early-stage Lung Adenocarcinoma. (December 2016) - Kadota, Kyuichi; Sima, Camelia S.; Arcila, Maria E.; Hedvat, Cyrus; Kris, Mark G.; Jones, David R.; Adusumilli, Prasad S.; Travis, William D.
Abstract : The potential clinical impact of KRAS and epidermal growth factor receptor ( EGFR ) mutations has been investigated in lung adenocarcinomas; however, their prognostic value remains controversial. In our study, we sought to investigate the prognostic significance of driver mutations using a large cohort of early-stage lung adenocarcinomas. We reviewed patients with pathologic early-stage, lymph node–negative, solitary lung adenocarcinoma who had undergone surgical resection (1995 to 2005; stage I/II=463/19). Tumors were classified according to the IASLC/ATS/ERS classification and genotyped by Sequenom MassARRAY system and polymerase chain reaction–based assays. In stage I disease, the Kaplan-Meier method and cumulative incidence of recurrence analyses were used to estimate the probability of overall survival (OS) and recurrence, respectively. Of all, 129 (27%) patients had mutations in KRAS, 86 (18%) in EGFR, 8 (2%) in BRAF, 8 (2%) in PIK3CA, 4 (1%) in NRAS, and 1 (0.2%) in AKT1 . EGFR L858R mutation correlated with lepidic predominant histology ( P =0.006), whereas exon 19 deletion correlated with acinar predominant histology ( P <0.001). EGFR mutations were not detected in invasive mucinous adenocarcinomas ( P =0.033). The 5-year OS of patients with KRAS -mutant tumors was significantly worse (n=124; 5-year OS, 63%) than those with KRAS wild-type (n=339; 77%; P <0.001). In solid predominant tumors, KRAS mutations correlated with worse OS ( P =0.008) and increased risk of recurrence ( P =0.005). On multivariate analysis, KRAS mutation was an independent prognosticator of OS in all patients (hazard ratio, 1.87; P <0.001) and recurrence in solid predominant tumors (hazard ratio, 4.73; P =0.012). In patients with resected stage I lung adenocarcinomas, KRAS mutation was an independent prognostic factor for OS and recurrence, especially in solid predominant tumors.